A subcortical variant of dementia with Lewy bodies?. (December 2021) - Philippi, Nathalie; Durand, Hélène; Noblet, Vincent; Botzung, Anne; Blanc, Frédéric
Abstract: Background: Even though Dementia with Lewy bodies (DLB) is the second most frequent neurodegenerative disease after Alzheimer's disease (AD), work is still needed on the definition of its clinical and radiological variants. The objective of the present work is to discuss the existence of a subcortical variant of DLB based on two previous studies. In the first study, the objective was to test the existence of a subcortical atrophy, contrasting with overall preserved cortex in DLB patients. In the second study, we described a series of DLB patients with an initial presentation including marked subcortical atrophy suggestive of normal pressure hydrocephalus (NPH). Method: In the first study, we included 55 DLB patients and compared their cerebral volumes to those of 51 AD patients and to those of 17 matched healthy control subjects (CS). We examined the ratio of the total ventricular volume (TVV) against the total cortical volume (Cortex), extracted using freesurfer. In the second study, we retrospectively compared the profile of 21 DLB patients fulfilling the criteria of possible NPH on initial presentation, to those of 13 patients with probable NPH. Result: In the first study, we found that DLB patients had a significantly higher TVV/Cortex ratio compared to both CS and AD patients. In the second study, we highlighted that some DLB patients have a clinical and radiological profile suggestive of NPH. DLB patients had a marked subcortical atrophy, with not significance difference in the dilatation of lateral ventricles and third ventricle compared to HPN patients, though they had a less acute callosal angle and less fourth ventricular dilatation. Conclusion: DLB is characterized by a subcortical atrophy contrasting with relatively preserved cortex, so marked in some cases that it might evoke ventricular dilatation. Together the two studies suggest the existence of a subcortical variant of DLB, with a clinical presentation and marked subcortical atrophy suggestive of NPH.